ORTHOGONAL TEST OPTIMUM RESEARCH FOR THE BOTTOM SLEW PLATFORM OF BELT CONVEYER - LIAO XiangHui; WEI ShiLong; LIU Huan; ZHAO Chu; XI MingLong (Jixie qiangdu, 2015)
A orthogonal test optimum design methodology was applied in the intensity analysis of shuttle belt conveyer slewing bearing,the finite element analysis was used to analyze the structure of the belt conveyer’s lower supported structure in the condition of initial design. According to the condition that its stiffness meet for the requirements,but the strength can’t meet,four factors which is the muscle thickness,the rib number,the rib fillet radius and the thickness of upper cover plate was selected. Then experimental analysis of the structure within different factors was carried out using orthogonal test optimization design. By the analysis the index evaluation of each factor was gotten in this paper. At last the optimum factor combination was provided to make the stiffness. The optimization results show that the performance of the lower bearing’intensity can be improved significantly,the study can also provide a theoretical basis to optimize the same structure design.